Community-Level Factors Associated with Body Mass Index Among Pakistani School-Aged Adolescents - Moazzam Tanveer, Umar Tanveer, Mubeen Afzal, Nasrullah Rana, Rashid Nagra, Waqar Anjum, Musa Haseeb (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To investigate the most recent estimates of underweight, overweight, and obesity prevalence with association of community-level factors in Pakistani school-aged adolescents aged 12 to 17 years. Methods: A cross-sectional study was conducted using a convenience sampling approach with 1,997 Pakistani from 40 schools in central Punjab province. The CDC US 2000 was used to define underweight < 5th percentile BMI, overweight 85th ≤ BMI to < 95th percentile BMI, and obese 95th percentile ≤ BMI, the Chi-square test was used. The Pearson correlation coefficient (r) was used to determine the correlation. The statistical significance level was set at p < 0.05. Results: prevalence of underweight U/W, overweight O/W, and obesity O/B was (23.5%, 4.6%, and 6.9%, respectively. There were no chances for students to engage in physical activity in the community, according to 72.9% of parents. Conclusion: Underweight, overweight, and obesity were prevalent among Pakistani school-aged adolescents. The community-based characteristics we discovered here have detrimental influences on school going adolescents’ health. The relationship between weight-status, behavioral, and other health variables should also be investigated in future research using longitudinal or interventional approaches. Keywords: Body Mass Index, School-aged adolescents, Community-Level